Coupling between Voltage Sensors and Activation Gate in Voltage-gated K(+) Channels - Lu, Zhe (The Rockefeller University Press, 2002)
Current through voltage-gated K(+) channels underlies the action potential encoding the electrical signal in excitable cells. The four subunits of a voltage-gated K(+) channel each have six transmembrane segments (S1–S6), whereas some other K(+) channels, such as eukaryotic inward rectifier K(+) channels and the prokaryotic KcsA channel, have only two transmembrane segments (M1 and M2). A voltage-gated K(+) channel is formed by an ion-pore module (S5–S6, equivalent to M1–M2) and the surrounding voltage-sensing modules. The S4 segments are the primary voltage sensors while the intracellular activation gate is located near the COOH-terminal end of S6, although the coupling mechanism between them remains unknown. In the present study, we found that two short, complementary sequences in voltage-gated K(+) channels are essential for coupling the voltage sensors to the intracellular activation gate. One sequence is the so called S4–S5 linker distal to the voltage-sensing S4, while the other is around the COOH-terminal end of S6, a region containing the actual gate-forming residues.